2022
DOI: 10.1371/journal.pone.0271355
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii complex, national laboratory-based surveillance in South Africa, 2017 to 2019

Abstract: Objective We aimed to provide an analysis of A. baumannii complex (ABC) isolated from blood cultures in South Africa. Materials and methods ABC surveillance was conducted from 1 April 2017 to 30 September 2019 at 19 hospital sites from blood cultures of any age and sex. Organism identification was performed using the MALDI-TOF MS and antimicrobial susceptibility testing (AST), MicroScan Walkaway System. We confirmed colistin resistance with Sensititre, FRCOL panel, and selected for whole-genome sequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…These findings are similar to the findings in the South African surveillance data of A. baumannii complex bacteraemia in 2017 until 2019 where the majority of the patients were paediatrics. 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to the findings in the South African surveillance data of A. baumannii complex bacteraemia in 2017 until 2019 where the majority of the patients were paediatrics. 30 …”
Section: Resultsmentioning
confidence: 99%
“…These findings are similar to the findings in the South African surveillance data of A. baumannii complex bacteraemia in 2017 until 2019 where the majority of the patients were paediatrics. 30 Pseudomonas species were generally more susceptible to the antimicrobials tested than were Acinetobacter species. The susceptibility to the two commonly used antipseudomonal agents, piperacillin-tazobactam and ceftazidime was 83% and 86%, respectively.…”
Section: Antimicrobial Susceptibility Pattern Of the Non-fermenting G...mentioning
confidence: 89%
“…Several studies have identified risk factors associated with extensively drug-resistant Acinetobacter baumannii infections (XDRABIs) in neonatal units. A. baumannii is a difficult pathogen to eradicate once present in a hospital setting given its ability to form strong biofilms [ 27 ]. Perovic et al reported >4800 cases of A. baumannii from 2017 to 2019, with the majority (60%) of cases from Gauteng province and 41% occurring in infants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%